Comparison of outcomes across low-intensity psychological interventions for depression and anxiety within a stepped-care setting: A naturalistic cohort study using propensity score modelling - Richards, Derek (My University, 2022)
Low-intensity interventions for common mental disorders (CMD) address issues such as clinician shortages and barriers to accessing care. However, there is a lack of research into their comparative effectiveness in routine care. We aimed to compare treatment effects of three such interventions, utilizing four years' worth of routine clinical data. Users completing a course of guided self-help bibliotherapy (GSH), internet-delivered cognitive behavioural therapy (iCBT) or psychoeducational group therapy (PGT) from a stepped-care service within the NHS in England were included. Propensity score models (stratification and weighting) were used to control for allocation bias and determine average treatment effect (ATE) between the interventions. 21,215 users comprised the study sample (GSH = 12,896, iCBT = 6862, PGT = 1457). Adherence-to-treatment rates were higher in iCBT. All interventions showed significant improvements in depression (PHQ-9), anxiety (GAD-7) and functioning (WSAS) scores, with largest effect sizes for iCBT. Both propensity score models showed a significant ATE in favour of iCBT versus GSH and PGT, and in favour of GSH versus PGT. Discernible differences in effectiveness were seen for iCBT in comparison with GSH and PGT. Given variance in delivery mode and human resources between different low-intensity interventions, building on these findings would be valuable for future service provision and policy decision making.
PUBLISHED
Keywords: anxiety; depression; guided self-help; internet-delivered cognitive behavioural therapy; low-intensity intervention; Digital Engagement; Clinical Psychology; Emotional/Mental Health